Extended criteria donor lung reconditioning with the organ care system lung: a single institution experience. (13th November 2018) - Schiavon, Marco; Faggi, Giulio; Rebusso, Alessandro; Lunardi, Francesca; Comacchio, Giovanni; Di Gregorio, Guido; Feltracco, Paolo; Gregori, Dario; Calabrese, Fiorella; Marulli, Giuseppe; Cozzi, Emanuele; Federico, Rea
Summary: Lung transplantation is a life‐saving procedure limited by donor's availability. Lung reconditioning by ex vivo lung perfusion represents a tool to expand the donor pool. In this study, we describe our experience with the OCS™ Lung to assess and recondition extended criteria lungs. From January 2014 to October 2016, of 86 on‐site donors evaluated, eight lungs have been identified as potentially treatable with OCS™ Lung. We analyzed data from these donors and the recipient outcomes after transplantation. All donor lungs improved during OCS perfusion in particular regarding the PaO2 /FiO2 ratio (from 340 mmHg in donor to 537 mmHg in OCS) leading to lung transplantation in all cases. Concerning postoperative results, primary graft dysfunction score 3 at 72 h was observed in one patient, while median mechanical ventilation time, ICU, and hospital stay were 60 h, 14 and 36 days respectively. One in‐hospital death was recorded (12.5%), while other two patients died during follow‐up leading to 1‐year survival of 62.5%. The remaining five patients are alive and in good conditions. This case series demonstrates the feasibility and value of lung reconditioning with the OCS™ Lung; a prospective trial is underway to validate its role to safely increase the number of donor lungs.